If it's not what You are looking for type in the equation solver your own equation and let us solve it.
36-c=42
We move all terms to the left:
36-c-(42)=0
We add all the numbers together, and all the variables
-1c-6=0
We move all terms containing c to the left, all other terms to the right
-c=6
c=6/-1
c=-6
| O=3x-x | | y=6-1+(-2) | | 8x-3-5x=2x | | -4p+23=11 | | 10r-3=9r-6-5 | | 5(2w-3)+10=3w+16 | | 3(7x+5)=2x-9 | | 12+2h=992 | | 6x-2=19=3x | | C=40/3x+20,R=15x | | 3(x+4)=2x-4 | | y+(-14)=-13 | | −1+x=4 | | -6b-3=-2b+9 | | 6=n/4+4 | | 6g+17=71 | | 42c=36 | | -10-5p+9=9-6p | | 36+c=42 | | -10-2s=4s+8 | | -8/3x+1=13/3+2/3x | | x+19=5x+17 | | 82(2x+8)=28(5x-4) | | f(70)=4(70)-2 | | 6m-7=5+10m | | f(64)=4(64)-2 | | 42+c=36 | | 5n=5=50 | | x-(7/11-x)=2/11 | | 10/x=5/25 | | -10-5h=10-h | | 7x+11+2x+2=4x-28 |